Effects of dietary antioxidants on training and performance in female runners - Braakhuis, A. J.; Hopkins, W. G.; Lowe, T. E. (European Journal of Sport Science, 2014)
Exercise-induced oxidative stress is implicated in muscle damage and fatigue which has led athletes to embark on antioxidant supplementation regimes to negate these effects. This study investigated the intake of vitamin C (VC) (1 g), blackcurrant (BC) juice (15 mg VC, 300 mg anthocyanins) and placebo in isocaloric drink form on training progression, incremental running test and 5-km time-trial performance. Twenty-three trained female runners (age, 31±8 y; mean±SD) completed three blocks of high-intensity training for 3 wks and 3 days, separated by a washout (~3.7 wks). Changes in training and performance with each treatment were analysed with a mixed linear model, adjusting for performance at the beginning of each training block. Markers of oxidative status included protein carbonyl, malondialdehyde (in plasma and in vitro erythrocytes), ascorbic acid, uric acid and erythrocyte enzyme activity of superoxide dismutase, catalase and glutathione peroxidase were analysed. There was a likely harmful effect on mean running speed during training when taking VC (1.3%; 90% confidence limits ±1.3%). Effects of the two treatments relative to placebo on mean performance in the incremental test and time trial were unclear, but runners faster by 1 SD of peak speed demonstrated a possible improvement on peak running speed with BC juice (1.9%; ±2.5%). Following VC, certain oxidative markers were elevated: catalase at rest (23%; ±21%), protein carbonyls at rest (27%; ±38%) and superoxide dismutase post-exercise (8.3%; ±9.3%). In conclusion, athletes should be cautioned about taking VC chronically, however, BC may improve performance in the elite.